Housewives Environmental Awareness in Household Solid Waste Management - Gilbert Givano; Yunita Ismail (Journal of Environmental Engineering and Waste Management, 2020)
Waste generation in recent years has been increasing. The main problem is in the lack of environmental awareness. Awareness can be influenced by behavior, knowledge and income. This research wants to find out whether these 3 factors have an influence to the awareness of housewives who manage their household waste that live in residential area partially and fully. Questionnaires using likert scale that have undergone validity and reliability test were distributed online using Google Form to 100 housewives. Data were analyzed using descriptive analysis and Multiple Linear Regression. Results showed that behavior and knowledge have positive significant influence toward awareness while income has no significance towards awareness on the respondents.